Ta'u-sug-English Tagalog dictionary - Jawali, Hamsali S. 1947- (National Bookstore, 2006)
This dictionary of Ta'usug, English and Tagalog languages is a trilingual dictionary that is designed to help bridge the communication gap between the Tagalog speaking Filipinos and the Ta'usug. This work by Dr. Hamsali Jawali is an entirely new work. The author approached his task with a deep sense of responsibility for updating the Ta'usug language with the inclusion of letters, which the past authors of Ta'usug-English dictionaries failed to consider. He intended to bring back the original sound, intonation and syllabication of the native Ta'usug speakers. This dictionary also has the most comprehensive and complete entries of words, alphabetically arranged, and their appropriate meanings in English and Tagalog. Included also in every entry are example of sentences in which the term is used.